Predictive directional measurement volatility spillovers between the US and selected Asian Pacific countries - Heitham Al-Hajieh (Cogent Economics & Finance, 2023)
Since portfolio management relies on the association of portfolio diversification, analyzing the spillover between the United States (US) and Asian-Pacific financial markets has become more critical. If Asian stock markets have low or negative correlations with each other and/or the US market, global investors may benefit from diversification. This study examines the return and volatility spillover between the S&P 500 and 12 Asian stock markets using weekly data from January 2000 to February 2020. DECO-GARCH models are employed to measure volatility transmission between markets. A generalized VAR, variance decomposition, and spillover index is employed to investigate the directional spillover across the sample, allowing for a focus on the interdependence of the conditional returns, conditional volatility, and conditional correlations between the stock markets. Hedge ratios and portfolio weights use to examine the results' implications for international portfolio diversification and risk management. The study calculates the effectiveness of hedging equities portfolios between markets, using the beta hedge approach to minimize the risk of this stock market index returns portfolio. The results demonstrate that Hong Kong and Singapore have a clear direction of a return to other stock markets, whereas China has a clear net recipient. The US market does not provide a superior hedging ratio for Asia-Pacific nations. For other stock markets, India, Hong Kong, and New Zealand have the best hedge ratios, portfolio weights, and hedging efficacy. Finally, this research raised the information linked between the stocks market index and can also apply to improve international portfolio by re-considering the cheapest hedging markets and improving the trading strategies in international markets.
Keywords: C58; F36; G1; G11; G17; 330; Asia Pacific stock markets; DECO-GARCH model; directional spillover index; financial market contagion; hedging equity portfolios